Leveraging migration for Africa : remittances, skills, and investments - Ratha, Dilip (Washington, DC : World Bank, 2011)
The book is a joint effort led by the African Development Bank and the World Bank and a comprehensive publication on harnessing migration, remittances, and other diaspora resources for the development of Africa. This volume contributes to a greater understanding of migration and its potential role in Africa's development.
Includes bibliographical references and index.
rua 08/05/13
Loans
Keywords: Emigrant remittances; African diaspora; Investments, Foreign; Economic development; Emigration and immigration - economic aspects; Africa